Characterization of the levels and G-protein coupling of adenosine A2A receptors in hippocampus and striatum of transgenic rats overexpressing adenosine A2A receptors in the brain - Bento, Marta Leal, 1992- (2020)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2016